Exploring the Relationship Between Employee Casualization and Workplace Productivity in Selected Manufacturing Firms in Edo State, Nigeria: A Contemporary Sociological Analysis - Akhigbe, Charles Monday (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
The essence of organization productivity is profits maximization. Achieving this requires the efficiency of staff output and in cases where more hands are needed, casual workers are engaged to increase production output and this can only be sustained when there are good relationships within the organization space. Therefore, this study seeks to examine the relationship Between Employee Casualization and Workplace Productivity in Selected Manufacturing Firms in Edo State. The Labour Market Segmentation theory by Michael Piore and Peter Doeringer were adopted for the study. Been a cross-sectional study, a sample size of 405 respondents were systematically selected for the study and both qualitative and quantitative instrument were used complementarily for the study. Finding from the study revealed that employee is associated with generally high levels of perceived productivity, largely sustained by supervisory support, motivation, and cordial management–employee relations. Motivation and harmonious relations enhance efficiency but persistent concerns about job security and unequal treatment remain. Based on this, conclusion and advocacy were deduced. Keywords: Casual Workers, Casualization, Management, Productivity